Simulated gastric hydrolysis and developmental toxicity of dimethyltin bis(2-ethylhexylthioglycolate) in rats - Kirf, Dominik; Costlow, Richard; Nasshan, Hans; Frenkel, Peter; Mondimore, Donna (Frontiers in Toxicology, 2023)
Dimethyltin dichloride is used as the putative toxophore for dimethyltin bis-alkylthio esters in a read-across approach. Recent chemical and toxicological investigations challenges this read across as data on dioctyltin bis(2-ethylhexyl thioglycolate) and dibutyltin bis(2-ethylhexyl thioglycolate) showed the dialkyltin thioglycolates do not generate dialkyltin dichloride. Results obtained by 119Sn-NMR spectroscopy demonstrated that dimethyltin bis(2-ethylhexyl thioglycolate), the smallest commercially manufactured dialkyltin thioester molecule of this kind, hydrolyzed to dimethyltin chloro-(2-ethylhexyl) thioglycolate under simulated gastric conditions. These studies did not detect dimethyltin dichloride. Dimethyltin bis(2-ethylhexyl thioglycolate) was administered orally to timed-pregnant Wistar-Han rats in an Arachis oil vehicle at 5, 10, and 25 mg/kg/day [Gestation Day 6 (GD6) through GD20] with no maternal deaths observed. At 25 mg/kg/day treatment statistically significant reductions occurred in feed consumption (−9%), maternal body weight (−2.4%) and adjusted maternal weight gain (−68%). There were no adverse gestational findings. Maternal thymus weight was significantly reduced in rats at 25 mg/kg in the absence of changes in hormone levels of T3, T4 or TSH. There were no effects on fetal growth, no dose-dependent pattern of external, visceral, or skeletal malformations and no toxicologically relevant increase in anatomical variations at any dose group. Based on the obtained experimental data it is concluded that dimethyltin bis(2-ethylhexyl thioglycolate) forms dimethyltin chloro-(2-ethylhexyl thioglycolate), not dimethyltin dichloride, in the stomach environment at pH 1.2, and dimethyltin bis(2-ethylhexyl thioglycolate) was not teratogenic nor fetotoxic in rats. The maternal NOAEL was 10 mg/kg/day, and the developmental NOAEL was 25 mg/kg/day, the high dose. The maternal LOAEL was 25 mg/kg/day based on decreased food consumption, lower adjusted mean body weight gain and reduced maternal thymus weight.